Tourism Village Management in Bali by Traditional Villages Based on Local Wisdom in the New Normal Era - I Wayan Wesna Astara; Putu Ayu Sriasih Wesna (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2023)
Traditional villages in Bali have the potential to become tourist destinations that benefit the local community. Culture and customs are what set apart traditional villages. The legal politics of the Bali tourist village have deteriorated into the new normal. This research aims to develop a tourist village model, a new theory for elaborating Balinese cultural values based on local wisdom values, a creative economy, and human resource management during the COVID-19 pandemic. The research method is a qualitative descriptive empirical legal analysis based on a socio-anthropological approach and law sociology, supplemented with cultural studies. The findings revealed that the value of local wisdom in the traditional village adds value to a tourist village in Bali. The Ceking traditional village's tourist rice terraces are appealing due to the culture of farmers becoming a tourist village. The Penglipuran traditional village's artistic potential, social capital, nature, and local wisdom are the codification of culture in power politics. Tourism is a helpful tool for economic development. Bali must explore the potential for increased innovation and community participation as a tourist destination by using traditional villages as a buffer for culture, Hinduism, and local wisdom. Furthermore, Bali tourism is exceptionally vulnerable to health concerns that affect tourism and ecotourism activities.